СРЕДА АСПЕКТОЛОГИЧЕСКОГО ДУАЛИЗМА ДЕЙСТВИЙ (Филолошке студије, 2019)
The paper deals with questions of defenition of the type of the environment of the aspectological meaning. In the center of author’s attention there is the aspectological dualism of actions demonstrated by the means of different levels in the German language. The determination of the means of the category of type in the German language has been oriented on Slavic aspectology for a long time.